Health, nutritional condition, and productivity of female moose (Alces alces) in Northwestern Ontario - Crouse, John Alan (2003)
Creation or maintenance of moose habitat through logging requires an understanding of how particular timber-harvest practices affect nutritional interactions of adult females and their subsequent production of young. I compared ultrasonographic fat measurements of free-ranging adult female moose in northwestern Ontario, Canada, 1998-2001, inhabiting two forest management regimes; a modified clear-cut, following the Timber Management Guidelines for the Provision o f Moose Habitat, and an unmodified, progressive, and contiguous clear-cut. I also determined pregnancy and in utero twinning by radioimmunoassay of pregnancy-specific protein B (PSPB) and compared the number of expected calves born to the number of calves surviving to winter. As an adjunct to evaluation of reproductive performance, I also examined blood parameters, hair mineral content, and stress hormone metabolite concentration in feces. For these comparisons to be made, however, reference ranges for blood and hair parameters needed to be established and the effects of handling, individual, temporal, and spatial factors on blood parameter variability measured. Likewise, the radioimmunoassay used to quantify stress hormone metabolites in feces had not been previously used in moose and the affinity of the antibody to the fecal glucocorticoid (GC) metabolites of moose was unknown. In Chapter 1, Validation o f a generalized fecal glucocorticoid assay fo r use in moose, I investigated whether a commercially available multi-species assay (ICN Biomedicals) accurately reflected acute adrenal activation in moose. Recent development of assays for GC metabolites has provided a non-invasive means to assess a variety of human-induced disturbances and environmental conditions on free-ranging animals. Fecal samples are easy to collect year-round and provide an integrated reflection of all GC secretion over a period of time prior to sample collection; however, species-specific differences in steroid metabolism necessitate validation of the assay used to quantify GC concentration. I pharmacologically challenged 2 captive-raised moose (1 male and 1 female) with adrenocorticotropin hormone (ACTH). A change in fecal GC metabolite levels was detected at 15 and 22 hours after the administration of the ACTH and levels remained elevated for 12 and 50 hours, respectively. Accuracy and parallelism tests demonstrated there was negligible interference from other substances in the feces and that the antibody binds with serially diluted fecal GC metabolite extracts in a dose-dependent manner. I concluded the ICN Biomedicals’ antibody could be used to detect a stress response in moose. Further study will be required to define seasonal patterns in adrenal activity, measure response to different types of stress, and evaluate the consequences of chronically elevated stress hormones. In Chapter 2, Comparative health status, nutritional condition, and productivity of female moose in northwestern Ontario under two forest management regimes, the age structure (assessed by tooth wear), body size, and manner in which animals were handled were shown to be similar between landscape treatments. Reference ranges generated for blood chemistry, hematology, and hair mineral content are presented. After controlling for the effects of handling and sampling year, body fat and/or landscape treatment explained little of the variance in these parameters. In 1999-2000,1 collected feces and evaluated stress hormone metabolite concentrations. Values were similar between landscape treatments and comparable to values observed in wild Alaskan moose during mid-winter. Because fecal metabolites represent stress hormone secretion over the previous 1-2 days, the values obtained are unaffected by capture stress making this technique suitable for monitoring adrenal activity in free-ranging moose. February body fat stores in adult females averaged 8.54% and exhibited little annual variation. Successfully raising a calf to winter modestly affected lipid reserves (8 vs. 9%) and apparently did not affect subsequent reproductive effort. Nutritional condition and intrauterine fecundity were similar between landscape treatments. Estimates exceeding 165 calves in utero/100 cows were indicative of populations below K carrying capacity. Calf survival to winter (Jan - Feb) was greater in the clear-cut landscape modified by the Timber Management Guidelines fo r the Provision of Moose Habitat than the progressive, contiguous clear-cut (67.3 calves/100 cows vs. 44.2 calves/100 cows) however, which suggested environmental factors affecting calf survival were different between the 2 landscape treatments.